KONTRIBUSI KETERAMPILAN MEMBACA PEMAHAMAN TERHADAPKETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 25 PADANG - Arbi, Maharani Dwi Putri; Thahar, Harris Effendi; Emidar, Emidar (Universitas Negeri Padang, 2018)
ABSTRACTÂ The aim of this research was to describe the contribution of reading comprehension to the writing skill in the exposition text on the eight grade students of SMP Negeri 25 Padang. This research is a quantitative research with descriptive method. The sample in this study amounted to 40 students. The data is score of exposition text writing skill test result and reading comprehension test result. Based on data analysis and discussion, the following three things are obtained. First, the exposition text writing skill test result of the eight grade students of SMP Negeri 25 Padang is in good qualification (81,50). Second, the reading comprehension skill test result on the eight grade students of SMP Negeri 25 Padang is in good qualification (81,39). Third, the reading comprehension skill has 43,03% contribution to the writing skill of the exposition text on eight grade students of SMP Negeri 25 Padang and the rest (56,97%) influenced by other factors not examined in this research.Â Kata kunci: kontibusi, membaca pemahaman, menulis, teks eksposisiÂ